Teachers’ Understanding and Constraints of Global Diversity Character Learning in Early Childhood Education - Munawar, Muniroh; Alfiah, Alfiah; Nur Aini, Aurora (LP. Ma'arif Janggan Magetan, 2025)
The current research aims to describe teachers’ understanding and constraints of global diversity character learning in early childhood education (ECE), especially at the kindergarten level (educational services for children aged 4 – 6 years) seen from several factors, namely: a) kindergarten teachers' understanding of the global diversity concept; b) use of global diversity teaching materials; c) types of global diversity teaching materials; and d) content of global diversity teaching materials. This study is a qualitative study with a descriptive approach. Data were collected through surveys, in-depth interviews, and documentation. The respondents of this study were 55 kindergarten teachers at School Mover who were members of IGTKI Central Java. The data analysis technique used was the Miles and Huberman interactive technique, which included data collection, data reduction, data presentation, conclusion, and data verification. The validity and reliability tests showed that this questionnaire item was valid and reliable. The results show that the majority of kindergarten teachers have a good understanding of the concept of global diversity dimension, use various types and forms of relevant teaching materials, the teaching materials used are from various trusted and varied references, and the content of the teaching materials has met the key elements of global diversity. However, teachers still experience obstacles in teaching materials because the existing teaching materials are less interesting for children. This study suggests the presence of more interesting teaching materials in the form of flipbooks, as flipbooks stimulate children's interest in learning global diversity characters.